Development and Validation of a Simple High Performance Liquid Chromatography/UV Method for Simultaneous Determination of Urinary Uric Acid, Hypoxanthine, and Creatinine in Human Urine - Nimanthi Wijemanne; Preethi Soysa; Sulochana Wijesundara; Hemamali Perera (International Journal of Analytical Chemistry)
Uric acid and hypoxanthine are produced in the catabolism of purine. Abnormal urinary levels of these products are associated with many diseases and therefore it is necessary to have a simple and rapid method to detect them. Hence, we report a simple reverse phase high performance liquid chromatography (HPLC/UV) technique, developed and validated for simultaneous analysis of uric acid, hypoxanthine, and creatinine in human urine. Urine was diluted appropriately and eluted with C-18 column 100 mm × 4.6 mm with a C-18 precolumn 25 mm × 4.6 mm in series. Potassium phosphate buffer (20 mM, pH 7.25) at a flow rate of 0.40 mL/min was employed as the solvent and peaks were detected at 235 nm. Tyrosine was used as the internal standard. The experimental conditions offered a good separation of analytes without interference of endogenous substances. The calibration curves were linear for all test compounds with a regression coefficient, r2>0.99. Uric acid, creatinine, tyrosine, and hypoxanthine were eluted at 5.2, 6.1, 7.2, and 8.3 min, respectively. Intraday and interday variability were less than 4.6% for all the analytes investigated and the recovery ranged from 98 to 102%. The proposed HPLC procedure is a simple, rapid, and low cost method with high accuracy with minimum use of organic solvents. This method was successfully applied for the determination of creatinine, hypoxanthine, and uric acid in human urine.